Pembuatan Sambungan Head Tube Sepeda Berbahan Plastik dengan Perkuatan Lapisan fiberglass : Indonesia - Santo Ajie Dhewanto; Reza Hanafi Arma Wijaya (Asian Journal of Innovation and Entrepreneurship, 2023)
A bicycle is a means of transportation used to move from one place to another. Bicycles are generally made of iron, steel, or other metal materials. In this study, an experiment was carried out to manufacture a bicycle using a combined material, namely an iron pipe laminated with a 3D print plastic material. The aim was to strengthen the connection parts to obtain maximum strength. The lamination method used in this study is hand lay-up. The hand lay-up method was chosen because it is the most straightforward and relatively inexpensive compared to other methods. In this study, the processes involved were the design process, the analysis process, the 3D printing process, the lamination process, the assembly process, and road testing. The simulation test results obtained the maximum stress at vertical loading of 29.24 MPa, horizontal loading of 130 MPa, and pedal loading of 9.92 MPa. These results show that the frame can withstand a load of 80 kg, pass through beams, and walk as far as 1 km, according to SNI standards. The bicycle can travel at a maximum speed of 26.2 km/hour. After several times of the head tube part usage, it held up well, and there were no cracks on each side. So that testing and design go according to plan and according to SNI.